2021
DOI: 10.1037/amp0000702
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and changes in subjective wellbeing during the early stages of the COVID-19 pandemic.

Abstract: The COVID-19 pandemic has considerably impacted many people's lives. This study examined changes in subjective wellbeing between December 2019 and May 2020 and how stress appraisals and coping strategies relate to individual differences and changes in subjective wellbeing during the early stages of the pandemic. Data were collected at 4 time points from 979 individuals in Germany. Results showed that, on average, life satisfaction, positive affect, and negative affect did not change significantly between Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
497
4
35

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(625 citation statements)
references
References 51 publications
56
497
4
35
Order By: Relevance
“…Therefore, our Hypothesis 1 on a general negative effect of the COVID-19 lockdown on satisfaction with work and family is confirmed. This result is in line with Zacher and Rudolph (2020), however, contradicts previous results for France by Recci et al (2020) and for Germany by Czymara et al (2020). Both of these studies, however, apply different methodologies than ours.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, our Hypothesis 1 on a general negative effect of the COVID-19 lockdown on satisfaction with work and family is confirmed. This result is in line with Zacher and Rudolph (2020), however, contradicts previous results for France by Recci et al (2020) and for Germany by Czymara et al (2020). Both of these studies, however, apply different methodologies than ours.…”
Section: Resultssupporting
confidence: 80%
“…Previous research either considers more general well-being measures as overall life satisfaction or negative feelings (e.g. Kivi et al 2020;Recci et al 2020;Zacher and Rudolph 2020), is restricted to specific sub-groups of the population (e.g. Kivi et al 2020;Zacher and Rudolph 2020), examines aggregated measures and not within-person changes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with studies linking the COVID-19 pandemic with declines in well-being around the globe. (5,24,25) Unlike other studies, our unique study design allowed us to examine population-based trends in the early psychological consequences of the COVID-19 pandemic as it unfolded using a large, representative, probability-based national sample on whom pre-pandemic mental and physical health data were available (collected before the pandemic and hence not susceptible to concerns about recall bias). Three key findings in particular offer insights about ways to encourage community resilience when addressing a crisis of this magnitude: support individuals with pre-existing conditions, mitigate secondary stress, and monitor extensive media exposure.…”
Section: Discussionmentioning
confidence: 99%
“…People differ in their reactions to the stressors caused by the COVID-19 pandemic. For example, Zacher and Rudolph (2020) found that perceiving this pandemic as more health threatening resulted in life dissatisfaction and emotional instability two months later. In contrast, emotional stability and self-control are associated with less stress during this pandemic (Flesia et al, 2020), and self-control is also associated with greater adherence to social distancing guidelines (Wolff et al, 2020).…”
Section: Motives For Security and Pleasurementioning
confidence: 99%